2012
DOI: 10.2298/abs1203935t
|View full text |Cite
|
Sign up to set email alerts
|

Karyological comparisons of the European hare (Lepus europaeus Pallas, 1778) from the Asian part of Turkey, with morphological contributions

Abstract: We focused on a comparison of karyological data for the European brown hare Lepus europaeus, from the Asian part of Turkey. In Turkish L. europaeus, the diploid number (2n), the fundamental number of chromosomal arms (FN) and the number of autosomal arms (FNa) were determined to be 2n=48, 84 and 80, respectively. The autosomes are composed of three pairs of metacentric chromosomes, four pairs of submetacentric chromosomes, ten pairs of subtelocentric chromosomes and six pairs of acrocentric chromosomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…As in other members of the genus, the karyotype of Lepus europaeus is characterized by a diploid number (2n) of 48 chromosomes (Schroder et al 1978;Arslan 2010;Tez 2012). A study in Turkey (localities İçel and Konya [south]) designated the fundamental number (FN) and the number of autosomal arms (FNa) as 90 and 86, respectively (Arslan 2010).…”
Section: Geneticsmentioning
confidence: 99%
See 2 more Smart Citations
“…As in other members of the genus, the karyotype of Lepus europaeus is characterized by a diploid number (2n) of 48 chromosomes (Schroder et al 1978;Arslan 2010;Tez 2012). A study in Turkey (localities İçel and Konya [south]) designated the fundamental number (FN) and the number of autosomal arms (FNa) as 90 and 86, respectively (Arslan 2010).…”
Section: Geneticsmentioning
confidence: 99%
“…The X chromosome was the largest submetacentric and the Y chromosome was acrocentric and the smallest in the set (Arslan 2010). Karyotypic analysis of L. europaeus in Turkey (localities Kayseri, Çankırı-Ilgaz, Nevşehir-Gülşehir [north and central]) determined the fundamental number of chromosomal arms (FN) and the number of autosomal arms (FNa) to be 84 and 80, respectively (Tez et al 2012). Furthermore, they classified the autosomal pairs as three metacentric, four submetacentric, 10 subtelocentric, and six acrocentric with the X chromosome as a large submetacentric chromosome, and the Y chromosome a small acrocentric chromosome.…”
Section: Geneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, Lepus europaeus has been recorded from different parts of Turkey by Steiner and Vauk (1966), Sert et al (2005), Sert (2006), and Tez et al (2012). Sert et al (2005) determined that the hares from the semiarid Şanlıurfa region, close to the Syrian border, had a distinct yellow pelage color, whereas all other Anatolian hares in their study represented more or less the European brown hare pelage type, with variably brownish colors interspersed with yellowish, black, and white elements, as well as grayish thighs.…”
Section: Discussionmentioning
confidence: 99%
“…Sert et al (2005), Ben Slimen (2006, and Stamatis et al (2008) examined genetic diversity of Anatolian hares by analyzing allozymes, microsatellites, and mtDNA. Demirbaş et al (2010) and Tez et al (2012) also studied some cytogenetical and morphological features of hares in Turkey. Initial studies of hares from Turkey suggested that there was only one species present, namely the brown hare, Lepus europaeus; however, those studies were restricted in sample sizes and geographical samples.…”
mentioning
confidence: 99%